Case report: Abscesses in children caused by invasive group A Streptococcus - Guo, Danchun; Zhuang, Shuting; Lu, Qinghua; Chen, Yunsheng; Meng, Qing; Sun, Lifang; Zheng, Yuejie; Wang, Wenjian; Yu, Dingle (Frontiers in Medicine, 2024)
Streptococcus is one of the common pathogens of suppurative infections. Invasive group A Streptococcus (iGAS) infections often develop from skin or soft tissue infections, and streptococcal toxic shock syndrome is considered the main cause of death in Chinese children with iGAS infectious disease. However, soft tissue infections caused by iGAS infections, especially the formation of abscesses, are relatively rare. A retrospective study was conducted, and pediatric in-patients who were diagnosed with an iGAS infection identified by cultures from normally sterile sites and treated in a tertiary hospital during 2016–2018 were included. A total of 14 patients were identified, which included 10 boys and four girls. The patients had an age range from 3 months to 10 years and were diagnosed with soft tissue infections and a formation of abscesses caused by iGAS infections. The most common sites of infections were the lower limbs. In five patients, the abscess was accompanied by fever, and the local soft tissue showed redness, swelling, tenderness, and an elevated skin temperature. Laboratory findings included an increased white blood cell (WBC) count in 12 patients, an increased C reactive protein (CRP) level in seven patients, and an increased erythrocyte sedimentation rate (ESR) in 10 patients. No patients had an elevated procalcitonin level. For all 14 patients, we performed puncture and drainage of abscesses, and cultured GAS from the drainage fluid. All children also received antibiotic treatment. During 2 months of follow-up, the patients' condition remained stable and no evidence of kidney or heart damage was observed. For pediatric patients with abscesses, early diagnosis, prompt treatment with incision and drainage, and immediate culture of the drainage fluid are important. Upon confirmation of an iGAS infection, β-lactam antibiotics should be given to provide effective treatment, and in some patients with poor therapeutic outcomes, the use of vancomycin as an alternative can achieve the desired results.